Product Competitiveness and Market Penetration in South Sulawesi: Mapping of Leading Export Commodities - Reviane, Indraswati Tri Abdi; Paddu, Abdul Hamid; Tajibu, Muhammad Jibril (Faculty of Economics and Business, Hasanuddin University, 2022)
This study analyzes the competitiveness and market penetration of the leading export commodities of South Sulawesi. The Klassen typology and Export Product Dynamic method used to map the leading export commodities based on the competitiveness, market penetration power, and export dynamic of each commodity. This study focuses on measuring competitiveness and market penetration of each leading export commodity by using the